Clinical activity of durvalumab for patients with advanced mismatch repair-deficient and repair-proficient endometrial cancer. A nonrandomized phase 2 clinical trial. Issue 6 (8th June 2021) - Antill, Yoland; Kok, Peey-Sei; Robledo, Kristy; Yip, Sonia; Cummins, Michelle; Smith, Deborah; Spurdle, Amanda; Barnes, Elizabeth; Lee, Yeh Chen; Friedlander, Michael; Baron-Hay, Sally; Shannon, Catherine; et al.
Abstract : Background: In this study, we assessed the activity of durvalumab, an antibody to programmed death ligand-1, in two cohorts of women with advanced endometrial cancers (AEC)—mismatch repair proficient (pMMR) and mismatch repair deficient (dMMR). Methods: A multicenter phase two study was performed in women with AEC with pMMR tumor progressing after one to three lines of chemotherapy and women with AEC with dMMR tumor progressing after zero to three lines of chemotherapy. Mismatch repair status was based on immunohistochemistry expression. All women received durvalumab 1500 mg given every 4 weeks until progression or unacceptable toxicity. The primary endpoint was objective tumor response by RECIST V.1.1 modified for immune-based therapeutics. Results: Seventy-one women were recruited: 35 dMMR and 36 pMMR. Median follow-up was 19 vs 21 months in dMMR versus pMMR, respectively. Median age was 67 years. Histology in dMMR versus pMMR included endometrioid (94% vs 57%) and serous (0% vs 31%) and was high grade in 26% vs 74%. The objective tumor response rate (OTRR) in the dMMR cohort was 47% (17/36, 95% CI 32 to 63), including 6 complete responses and 11 partial responses (PRs)) vs 3% in the pMMR cohort (1/35, 95% CI 1 to 15, PR). In the dMMR cohort, durvalumab was the first-line therapy in 58% (OTRR 57%) and the second-line therapy in 39% (OTRR 38%). Median progression-free survival was 8.3 months in the dMMR cohort vs 1.8 months in the pMMR cohort. The 12-month overall survival (OS) rate was 71% in dMMR vs 51% in pMMR, with median OS not reached for dMMR vs 12 months for pMMR. Immune-related adverse events occurred in 14 women, mostly grades 1–2. Conclusion: Durvalumab monotherapy showed promising activity and acceptable safety in AEC with dMMR regardless of prior lines of chemotherapy, but activity was limited in AEC with pMMR. Trial registration numbers: ANZGOG1601, ACTRN12617000106336, and NCT03015129 .